# Finite element heat equation on a single simplex?

I am currently trying to learn the finite element method. Ultimately, I want to solve the heat equation in arbitrary dimensions. For the purpose of this question, however, assume that I am interested in a 2-dimensional space. The heat equation looks like this:

$$\frac{dc}{dt}=K\Delta c$$

Now the tricky part of the question: I want to solve this equation only on a single, simplical element (e.g., in two dimensions a triangle consisting of three non-collinear nodes). Assume that I know the coordinates $$(x_1,y_1)$$, $$(x_2,y_2)$$, and $$(x_3,y_3)$$ of the nodes and their corresponding temperatures $$c_1$$, $$c_2$$, and $$c_3$$. Further assume that the parameter $$K$$ is known and isotropic and homogeneous (i.e., a scalar value). The system does not have any sources or sinks or flow over the boundaries.

Is it possible to solve the heat equation on such a simple system with the finite element method, or do I require more than one element?

• Working on it. Please be patient. I think the answer is yes : you can do it with just one element (triangle / three space-time tetrahedrons). – Han de Bruijn Apr 3 at 14:11
• The answer is below. Sorry that I didn't maintain the notation in your question, because that would mean that I had to make changes (at great risk) in my source material. So please replace $c \rightarrow T$ and take notice that e.g. $\Delta$ is a determinant (i.e. not your diffusion operator) in my answer. – Han de Bruijn Apr 6 at 18:58

For the purpose of keeping essentials and being consistent with my source material, I took the freedom to replace the OP's original equation by the following: $$\frac{dc}{dt}=K\Delta c \quad \rightarrow \quad \frac{\partial T}{\partial t} = \frac{\partial^2 T}{\partial x^2} + \frac{\partial^2 T}{\partial y^2}$$ This means that $$c \rightarrow T$$ and the physical constant is taken equal to unity, so $$K=1$$ .

## Linear Tetrahedron

Let's consider at first the simplest non-trivial finite element shape in 3-D, which is a linear tetrahedron. Piece of theory for the Linear Thetrahedron has been developed here:

The following formula is recalled from that MSE reference: $$T - T_0 = A.(x - x_0) + B.(y - y_0) + C.(z - z_0)$$ What kind of terms can be discretized at the domain of a linear tetrahedron? In the first place, the function $$T(x,y,z)$$ itself, of course. But one may also try on the first order partial derivatives $$\partial T / (x,y,z)$$. From the above definition of $$(A,B,C)$$ we have: $$\frac{\partial T}{\partial x} = A \quad ; \quad \frac{\partial T}{\partial y} = B \quad ; \quad \frac{\partial T}{\partial z} = C$$ Using the matrix expression which was found in the reference for $$(A,B,C)$$: $$\begin{bmatrix} \partial T / \partial x \\ \partial T / \partial y \\ \partial T / \partial z \end{bmatrix} = \begin{bmatrix} x_1-x_0 & y_1-y_0 & z_1-z_0 \\ x_2-x_0 & y_2-y_0 & z_2-z_0 \\ x_3-x_0 & y_3-y_0 & z_3-z_0 \end{bmatrix}^{-1} \begin{bmatrix} T_1-T_0 \\ T_2-T_0 \\ T_3-T_0 \end{bmatrix}$$

## Space-time elements

In 3-D space-time, the $$z$$-coordinate is replaced by time, the $$t$$-coordinate. This may be done as follows: $$x_3 = x_0 \; ; \; y_3 = y_0 \; ; \; z_0 = z_1 = z_2 = t_0 \; ; \; z_3 = t_3$$ Consequently we have: $$\begin{bmatrix} \partial T / \partial x \\ \partial T / \partial y \\ \partial T / \partial t \end{bmatrix} = \begin{bmatrix} x_1-x_0 & y_1-y_0 & 0 \\ x_2-x_0 & y_2-y_0 & 0 \\ 0 & 0 & t_3 - t_0 \end{bmatrix}^{-1} \begin{bmatrix} T_1-T_0 \\ T_2-T_0 \\ T_3-T_0 \end{bmatrix}$$ From which it follows that: $$\begin{bmatrix} \partial T / \partial x \\ \partial T / \partial y \end{bmatrix} = \begin{bmatrix} x_1-x_0 & y_1-y_0 \\ x_2-x_0 & y_2-y_0 \end{bmatrix}^{-1} \begin{bmatrix} T_1-T_0 \\ T_2-T_0 \end{bmatrix} \quad \Longrightarrow \\ \begin{bmatrix} \partial T / \partial x \\ \partial T / \partial y \end{bmatrix} = \begin{bmatrix} y_2-y_0 & -(y_1-y_0) \\ -(x_2-x_0) & x_1-x_0 \end{bmatrix}/\Delta \begin{bmatrix} T_1-T_0 \\ T_2-T_0 \end{bmatrix} \\$$ with $$\Delta = (x_1-x_0)(y_2-y_0)-(y_1-y_0)(x_2-x_0)$$ . And: $$\frac{\partial T}{\partial t} = \frac{T_3-T_0}{t_3-t_0}$$ This effectively means that the space-time tetrhahedron splits up into a triangle in space and a time-step. Two other space-time elements are defined by: $$x_4 = x_1 \; ; \; y_4 = y_1 \; ; \; z_0 = z_1 = z_2 = t_1 \; ; \; z_4 = t_4 \\ x_5 = x_2 \; ; \; y_5 = y_2 \; ; \; z_0 = z_1 = z_2 = t_2 \; ; \; z_5 = t_5$$ Giving the same triangle in space, but different tetrahedrons in space-time, so we also have: $$\frac{\partial T}{\partial t} = \frac{T_4-T_1}{t_4-t_1} \\ \frac{\partial T}{\partial t} = \frac{T_5-T_2}{t_5-t_2}$$ But the time steps themselves are equal : $$t_3-t_0 = t_4-t_1 = t_5-t_2 = \mbox{dt}$$ .

## Diffusion term

For the Linear Triangle there are two other references at MSE that might be useful:

The latter reference is about the diffusion term (which is $$K\nabla c$$ in your question). Search for differentiation matrix in the latter reference and find the following formula: $$\Delta \left[ \begin{array}{c} \partial f / \partial x \\ \partial f / \partial y \end{array} \right] = \left[ \begin{array}{ccc} +(y_2 - y_3) & +(y_3 - y_1) & +(y_1 - y_2) \\ -(x_2 - x_3) & -(x_3 - x_1) & -(x_1 - x_2) \end{array} \right] \left[ \begin{array}{c} f_1 \\ f_2 \\ f_3 \end{array} \right]$$ In a more abstract (operator) form this is read as: $$\begin{bmatrix} \partial/\partial x \\ \partial/\partial y \end{bmatrix} = \begin{bmatrix} +(y_2 - y_3) & +(y_3 - y_1) & +(y_1 - y_2) \\ -(x_2 - x_3) & -(x_3 - x_1) & -(x_1 - x_2) \end{bmatrix} / \Delta$$ The rest of the reference is about the diffusion term (which is $$K\Delta c$$ in your question).
Begin of quotes. When using a Finite Element method, the differential equation may be multiplied at first with an arbitrary (test)function. Subsequently the PDE is integrated over the domain of interest. Let the test function be called $$f$$, then: $$\iint f . \left[ \frac{\partial Q_x}{\partial x} + \frac{\partial Q_y}{\partial y} \right] \, dx dy = 0$$ Partial integration, or applying Green's theorem (which is the same), results in an expression with [zero] line-integrals over the boundaries and an area integral over the bulk field. The latter is given by: $$- \iint \left[ \frac{\partial f}{\partial x}.Q_x + \frac{\partial f}{\partial y}.Q_y \right] \, dx dy$$ Mind the minus sign. End of quotes.
With diffusion of heat, we have the following expressions for $$(Q_x,Q_y)$$: $$Q_x = \frac{\partial T}{\partial x} \quad ; \quad Q_y = \frac{\partial T}{\partial y}$$ Now I hope it is not difficult to see that the diffusion operator ends up as: $$-(\nabla\cdot\nabla) = - \begin{bmatrix} \partial/\partial x & \partial/\partial y \end{bmatrix} \begin{bmatrix} \partial/\partial x \\ \partial/\partial y \end{bmatrix}$$ And the differentiation matrix may be employed to get the numerical equivalent.

## Programming

All the theoretical ingredients are essentially there and we are ready to program:

program Galt;

type
vektor = array of double;
matrix = array of array of double;
var
x,y,T : vektor;
k : integer;

procedure element(x,y : vektor; var E : matrix);
{
Finite Element for Diffusion
}
var
ddg: array[1..2,1..3] of double;
i,j,m : byte;
x32,x21,x13,y23,y12,y31,h,DET : double ;
begin
x32 := x-x ; y23 := y-y ;
x13 := x-x ; y31 := y-y ;
x21 := x-x ; y12 := y-y ;
{
Partial differentiation d/dx, d/dy
at a triangle can be conveniently
represented by the so called

Differentiation Matrix:
---------------------- }
DET := x21*y31-x13*y12 ;
if DET = 0 then
begin
Writeln('Element: null triangle');
Halt;
end;
ddg[1,1] := y23/DET ; ddg[2,1] := x32/DET ;
ddg[1,2] := y31/DET ; ddg[2,2] := x13/DET ;
ddg[1,3] := y12/DET ; ddg[2,3] := x21/DET ;

SetLength(e,4,4);
{ Laplace equation: }
for i := 1 to 3 do
begin
for j := 1 to 3 do
begin
h := 0 ;
for m := 1 to 2 do
h := h+ddg[m,i]*ddg[m,j] ;
E[i,j] := h;
end;
end;
end;

procedure stap(x,y : vektor; dt : double; var T : vektor);
{
Single time-step
}
const
D : double = 1;
var
E : matrix;
f : vektor;
k,i : integer;
bij : double;
begin
element(x,y,E);
SetLength(f,4);
for k := 1 to 3 do
Write(T[k]);
Writeln;
for k := 1 to 3 do
begin
bij := 0;
for i := 1 to 3 do
bij := bij + E[k,i]*T[i];
f[k] := T[k] - D*bij*dt;
end;
for k := 1 to 3 do
T[k] := f[k];
end;

BEGIN
SetLength(x,4);
SetLength(y,4);
SetLength(T,4);
Random; Random;
Random; Random;
Random; Random;
for k := 1 to 3 do
begin
x[k] := Random;
y[k] := Random;
end;
T := 10; T := 0; T := 0;
while true do
begin
stap(x,y,0.01,T);
end;
END.


Output:

 1.00000000000000E+0001 0.00000000000000E+0000 0.00000000000000E+0000
8.61920953541079E+0000 1.33969080728511E+0000 4.10996573041039E-0002
7.60872336562710E+0000 2.17022299029973E+0000 2.21053644073171E-0001
6.84976940041965E+0000 2.68162359364645E+0000 4.68607005933898E-0001
6.26514037958233E+0000 2.99343622963065E+0000 7.41423390787021E-0001
5.80413089466921E+0000 3.18080816165291E+0000 1.01506094367787E+0000
5.43300384629370E+0000 3.29092935946325E+0000 1.27606679424305E+0000
5.12894722761363E+0000 3.35339081179384E+0000 1.51766196059253E+0000
4.87623530811445E+0000 3.38671052578895E+0000 1.73705416609660E+0000
4.66378311538872E+0000 3.40244436336416E+0000 1.93377252124711E+0000
4.48358247230717E+0000 3.40777490861061E+0000 2.10864261908222E+0000
4.32969660054942E+0000 3.40714131220967E+0000 2.26316208724091E+0000
4.19760933061891E+0000 3.40326490578317E+0000 2.39912576359792E+0000
4.08380003241469E+0000 3.39779418306767E+0000 2.51840578451765E+0000
3.98546274268985E+0000 3.39171005488102E+0000 2.62282720242914E+0000
...
3.33333333333369E+0000 3.33333333333338E+0000 3.33333333333296E+0000


Notes.
1. Use has been made of the fact that our Finite Element matrix is actually three pieces of an equivalent finite difference system of linear equations, each equation belonging to a node of the triangle. So we must have three time-steps as well.
2. Random choices have been tried until the element-matrix has positive entries on the main diagonal and negative off-diagonal. This (definitely) means that the accompanying triangle has no obtuse angles.
3. Choosing the time-step   dt   is an important issue that has not been elaborated here. For our purpose, it has been determined experimentally, in such a way that no instabilities are being observed in the output.

UPDATE. With hindsight, instead of three overlapping tetrahedrons, it is more convenient to consider just one space-time finite element, namely a triangular brick, like this one: It's an element with a triangle $$(0,1,2)$$ at the bottom and a triangle $$(3,4,5)$$ at the top. The edges $$(0,4),(1,5),(2,6),(3,7)$$ are perpendicular to both triangles, and: $$x_0 = x_3 \; , \; y_0 = y_3 \; , \; x_1 = x_4 \; , \; y_1 = y_4 \; , \; x_2 = x_5 \; , \; y_2 = y_5 \\ t_0 = t_1 = t_2 \; , \; t_3 = t_4 = t_5$$ The F.E. interpolation of the element is, in local coordinates, with $$(\xi,\eta) =$$ local 2-D space and $$\zeta$$ = local time: $$T = (1-\zeta)\left[(1-\xi-\eta).T_0+\xi.T_1+\eta.T_2\right]+\zeta\left[(1-\xi-\eta).T_3+\xi.T_4+\eta.T_5\right]$$ Likewise for the global coordinates $$T \rightarrow x,y,t\;$$ (: isoparametrics). Then the rest follows.

• Phew, wow. I can't begin to state how grateful I am that you invested so much of your time for this elaborate response. It will definitely take some time for me to digest your answer and delve through the references given above. Not just food for thought - a banquet =P – J.Galt Apr 6 at 20:23
• Your're quite welcome; thank you for the kind words. I'm still making changes in the answer though. You can keep track of these (I hope) in the revision history. – Han de Bruijn Apr 7 at 11:12

The OP writes: Ultimately, I want to solve the heat equation in arbitrary dimensions.
This is not essentially more difficult than solving the problem with two space dimensions. So here we go. Again, I took the freedom to replace the OP's original equation by the following, for $$3$$ dimensions: $$\frac{dc}{dt}=K\Delta c \quad \rightarrow \quad \frac{\partial T}{\partial t} = \frac{\partial^2 T}{\partial x^2} + \frac{\partial^2 T}{\partial y^2} + \frac{\partial^2 T}{\partial z^2}$$ This means that $$c \rightarrow T$$ and the physical constant is taken equal to unity, so $$K=1$$ .

## Theory

We shall take bigger steps and proceed with the matrix that has been displayed in the previous answer: $$\begin{bmatrix} \partial T / \partial x \\ \partial T / \partial y \\ \partial T / \partial z \end{bmatrix} = \begin{bmatrix} x_1-x_0 & y_1-y_0 & z_1-z_0 \\ x_2-x_0 & y_2-y_0 & z_2-z_0 \\ x_3-x_0 & y_3-y_0 & z_3-z_0 \end{bmatrix}^{-1} \begin{bmatrix} T_1-T_0 \\ T_2-T_0 \\ T_3-T_0 \end{bmatrix}$$ Now define: $$\begin{bmatrix} d_{11} & d_{12} & d_{13} \\ d_{21} & d_{22} & d_{23} \\ d_{31} & d_{32} & d_{33} \end{bmatrix} = \begin{bmatrix} x_1-x_0 & y_1-y_0 & z_1-z_0 \\ x_2-x_0 & y_2-y_0 & z_2-z_0 \\ x_3-x_0 & y_3-y_0 & z_3-z_0 \end{bmatrix}^{-1}$$ It follows that: $$\begin{bmatrix} \partial T / \partial x \\ \partial T / \partial y \\ \partial T / \partial z \end{bmatrix} = \begin{bmatrix} d_{11} & d_{12} & d_{13} \\ d_{21} & d_{22} & d_{23} \\ d_{31} & d_{32} & d_{33} \end{bmatrix} \begin{bmatrix} T_1 \\ T_2 \\ T_3 \end{bmatrix} - \begin{bmatrix} d_{11} & d_{12} & d_{13} \\ d_{21} & d_{22} & d_{23} \\ d_{31} & d_{32} & d_{33} \end{bmatrix} \begin{bmatrix} T_0 \\ T_0 \\ T_0 \end{bmatrix} \\ = \begin{bmatrix} d_{11} & d_{12} & d_{13} \\ d_{21} & d_{22} & d_{23} \\ d_{31} & d_{32} & d_{33} \end{bmatrix} \begin{bmatrix} T_1 \\ T_2 \\ T_3 \end{bmatrix} - T_0 \begin{bmatrix} d_{11} + d_{12} + d_{13} \\ d_{21} + d_{22} + d_{23} \\ d_{31} + d_{32} + d_{33} \end{bmatrix} \\ = \begin{bmatrix} - (d_{11} + d_{12} + d_{13}) & d_{11} & d_{12} & d_{13} \\ - (d_{21} + d_{22} + d_{23}) & d_{21} & d_{22} & d_{23} \\ - (d_{31} + d_{32} + d_{33}) & d_{31} & d_{32} & d_{33} \end{bmatrix} \begin{bmatrix} T_0 \\ T_1 \\ T_2 \\ T_3 \end{bmatrix}$$ So the $$3 \times 4$$ differentiation matrix is: $$\begin{bmatrix} \partial / \partial x \\ \partial / \partial y \\ \partial / \partial z \end{bmatrix} = \begin{bmatrix} - (d_{11} + d_{12} + d_{13}) & d_{11} & d_{12} & d_{13} \\ - (d_{21} + d_{22} + d_{23}) & d_{21} & d_{22} & d_{23} \\ - (d_{31} + d_{32} + d_{33}) & d_{31} & d_{32} & d_{33} \end{bmatrix}$$ And the numerical equivalent of the Laplace operator in 3-D is minus the transpose times the original, hence a $$4 \times 4$$ matrix: $$(\nabla\cdot\nabla) = - \begin{bmatrix} \partial / \partial x & \partial / \partial y & \partial / \partial z \end{bmatrix} \begin{bmatrix} \partial / \partial x \\ \partial / \partial y \\ \partial / \partial z \end{bmatrix}$$ Last but not least, time stepping is defined by: $$\left.\frac{\partial T}{\partial t}\right|_0 = \frac{T_4-T_0}{t_4-t_0} \quad ; \quad \left.\frac{\partial T}{\partial t}\right|_1 = \frac{T_5-T_1}{t_5-t_1} \\ \left.\frac{\partial T}{\partial t}\right|_2 = \frac{T_6-T_2}{t_6-t_2} \quad ; \quad \left.\frac{\partial T}{\partial t}\right|_3 = \frac{T_7-T_3}{t_7-t_3}$$ where the denominators are all the same. The finite element involved may be conceived as a four dimensional space-time brick with a tetrahedron $$(0,1,2,3)$$ at the bottom and a tetrahedron $$(4,5,6,7)$$ at the top. The edges $$(0,4),(1,5),(2,6),(3,7)$$ are perpendicular to both tetrahedrons.

## Practice

A robust matrix inversion routine is needed in addition. We take the one that is eplained in the following MSE reference:

Now all the theoretical ingredients are essentially there and we are ready to program (in Delphi Pascal).

program General;

Uses Nodig; { inverse(b : matrix; var q : matrix) }

type
vektor = array of double;
const
NDM : integer = 3; { space dimension }
dt : double = 0.1; { time step estimate }
var
crd,inv,ddg,E : matrix;
f,T : vektor;
i,j,k : integer;
h,bij : double;
begin
SetLength(crd,NDM,NDM);
{ Easy coordinates }
for i := 0 to NDM-1 do
begin
for j := 0 to NDM-1 do
begin
crd[i,j] := 0;
end;
end;
for i := 0 to NDM-1 do
begin
crd[i,i] := 1;
end;
{ See MSE reference }
inverse(crd,inv);
{ Differentiation matrix }
SetLength(ddg,NDM,NDM+1);
for i := 0 to NDM-1 do
begin
for j := 0 to NDM-1 do
begin
ddg[i,j+1] := inv[i,j];
end;
end;
for i := 0 to NDM-1 do
begin
h := 0;
for j := 0 to NDM-1 do
begin
h := h + inv[i,j];
end;
ddg[i,0] := - h;
end;
{ Element matrix for Delta }
SetLength(E,NDM+1,NDM+1);
for i := 0 to NDM do
begin
for j := 0 to NDM do
begin
h := 0;
for k := 0 to NDM-1 do
begin
h := h + ddg[k,i]*ddg[k,j];
end;
E[i,j] := h;
end;
end;
SetLength(f,NDM+1);
SetLength(T,NDM+1);
{ Temperature intialization }
for k := 0 to NDM do
T[k] := 0;
T := 1;
{ Time stepping }
while true do
begin
for k := 0 to NDM do
Write(T[k]:9:5);
Writeln;
for k := 0 to NDM do
begin
bij := 0;
for i := 0 to NDM do
bij := bij + E[k,i]*T[i];
f[k] := T[k] - bij*dt;
end;
for k := 0 to NDM do
T[k] := f[k];
end;
end.


Output:

  1.00000  0.00000  0.00000  0.00000
0.70000  0.10000  0.10000  0.10000
0.52000  0.16000  0.16000  0.16000
0.41200  0.19600  0.19600  0.19600
0.34720  0.21760  0.21760  0.21760
0.30832  0.23056  0.23056  0.23056
0.28499  0.23834  0.23834  0.23834
0.27100  0.24300  0.24300  0.24300
0.26260  0.24580  0.24580  0.24580
0.25756  0.24748  0.24748  0.24748
0.25453  0.24849  0.24849  0.24849
0.25272  0.24909  0.24909  0.24909
0.25163  0.24946  0.24946  0.24946
0.25098  0.24967  0.24967  0.24967
0.25059  0.24980  0.24980  0.24980
0.25035  0.24988  0.24988  0.24988
0.25021  0.24993  0.24993  0.24993
0.25013  0.24996  0.24996  0.24996
0.25008  0.24997  0.24997  0.24997
0.25005  0.24998  0.24998  0.24998
0.25003  0.24999  0.24999  0.24999
0.25002  0.24999  0.24999  0.24999
0.25001  0.25000  0.25000  0.25000
0.25001  0.25000  0.25000  0.25000
0.25000  0.25000  0.25000  0.25000


Notes.
1. It is claimed that this program works for arbitrary space-like dimensions NDM: adjust the constant.
2. It has been observed that diffusion works even better, numerically, for higher values of NDM.
3. With some precautions, the easy coordinates in the program can be replaced by "random" ones.
4. Defining a Finite Element mesh instead of a Single Simplex in multiple dimensions is quite another challenge.

• It is typical that in Quantum Mechanics the linear momentum operator is Hermitian, which means that the transpose $(\partial/\partial x)^T$ in Numerical Analysis is consistent with QM: $$\left(-i\hbar\frac{\partial}{\partial x}\right)^* = i\hbar\left(\frac{\partial}{\partial x}\right)^T= -i\hbar\frac{\partial}{\partial x}$$ – Han de Bruijn Apr 13 at 14:34